Analysis of Availability and Spatial Distribution Patterns and Accessibility of Health Facilities in Regional Development - Sedayu, Riswanto Agung; Sidabutar, Yuanita FD; Saherny, Sukma (Journal La Medihealtico, 2025)
This study aims to analyze the availability, spatial distribution patterns, and accessibility of health facilities in Batam Kota District in order to support regional development. The availability of health facilities in Batam Kota District consists of hospitals, health centers, sub-health centers, clinics, and pharmacies spread across various sub-districts. Spatial analysis methods are used to identify the distribution patterns of health facilities, while accessibility analysis is carried out by taking into account the distance and travel time from the center of the settlement. The results of the study indicate that health facilities in Batam Kota District have a clustered distribution pattern in hospitals and a random pattern in health centers, clinics, and pharmacies. Accessibility to health facilities is quite good, but there is an imbalance in the distribution of facilities, especially in sub-districts with high population density. SWOT analysis identifies the strengths, weaknesses, opportunities, and threats related to the development of health facilities in this area. In conclusion, there needs to be more equitable development of health facilities, additional medical personnel, and utilization of infrastructure to improve access and quality of health services, in order to support sustainable regional development in Batam Kota District.